Characteristics of heritage of industrial modernization and urban spatial distribution in Shenyang, China - Bingyu Sun; Konomi Ikebe (Journal of Asian Architecture and Building Engineering, 2023)
This study investigated the projects recorded in The Architectural Heritage of Modern China: Shenyang and documents of protected historical and cultural sites published by the Shenyang government from 1985 to 2020. According to fieldwork and a literature search, an original database with 153 heritage sites of industrial modernization in Shenyang was developed. For further investigation, the projects in this database were categorized by architectural function and structural type. According to historical development and changes in administration, the history of modernization in the designated era falls into four phases, and the core study area can be divided into four subareas. In this study, ArcGIS was used to make an entire distribution map, which was combined with the results of the categorization to analyze areas and obtain an overall picture of the distribution characteristics of Shenyang’s heritage of industrial modernization. The characteristics of the research objects were identified after categorization analysis of their age, function, structure, and spatial distribution in the database. Based on these results, a new evaluation of this heritage can be pursued, which can provide a basis for the future preservation and utilization of such heritage.